Study of The Effect of Leaching Time of Manganese Ore from Pujananting District, Barru Regency Using The Hydrometallurgical Method - Nurhawaisyah, Sitti Ratmi; Muhammad Fajrul; Muhammad Idris Juradi; Mubdiana Arifin; Suriyanto Bakri (Journal of Chemical Process Engineering, 2025)
In the mining industry, increasing the content of valuable minerals in the ore levels needs to be done to add economic value. One of the methods to increase copper ore levels is leaching using a sulfuric acid solution. The purpose of this study is to determine the effect of leaching time variations on manganese gain. Lysis was carried out using a sulfuric acid solution of 30 ml per leach, a sample weight of 20 gr for each leach, a grain size of -150 mesh, a stirring speed of 200 rpm with variations in leaching time of 90 minutes, 120 minutes, 150 minutes, 180 minutes. The filtrate results from the leachate were then analyzed using the Atomic Absorption Spectrophotometer (AAS). The results of this study obtained the dissolved Mn at a 90-minute runtime of 14.4045902%, at a 120-minute runtime of 14.4221077%, at a 150-minute runoff time of 14.4173441% and at a 180-minute runoff time of 14.4244638%. Based on the results of the study, the optimal time was obtained the highest dissolved Mn is at 180 minutes of leaching.